2019
DOI: 10.7150/ijms.30889
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acids enhance chemosensitivity through connexin 43 upregulation in murine melanoma models

Abstract: Chemotherapy is now in common use for the treatment of tumors; however, with tumor growth retardation comes the severe side effects that occur after a chemotherapy cycle. Eicosapentaenoic acids (EPA) used in combination with chemotherapy has an additive effects and provides a rationale for using EPA in tandem with chemotherapy. To improve the efficacy and safety of this combination therapy, a further understanding that EPA modulates with the tumor microenvironment is necessary. Connexin 43 (Cx43) is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Tumors can utilize multiple strategies to evade the immune response, requiring an appropriate method that involves a combination of targets to improve therapeutic outcomes. We explored the potential to enhance the tumor therapeutic response through Cx43 and IDO pathway inhibition in different tumor types including melanoma and lung cancer 25, 26. Recently, we also observed that PG2 could inhibit the expression of programmed cell death protein 1 ligand 1 (PD-L1) in tumor cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors can utilize multiple strategies to evade the immune response, requiring an appropriate method that involves a combination of targets to improve therapeutic outcomes. We explored the potential to enhance the tumor therapeutic response through Cx43 and IDO pathway inhibition in different tumor types including melanoma and lung cancer 25, 26. Recently, we also observed that PG2 could inhibit the expression of programmed cell death protein 1 ligand 1 (PD-L1) in tumor cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of resveratrol with cisplatin causes a potentiated apoptotic effect in vitro, and reduced tumor cell growth to a higher extent than cisplatin therapy alone in vivo (Cheng et al, 2015). Similar results were obtained using regular 5-FU anticancer therapy in combination with eicosapentaenoic acids (EPA) that upregulate Cx43, enhancing the drug cytotoxicity through the activation of mitogen-activated protein kinase (MAPK) signaling pathways (Yang et al, 2019). In addition, the bystander effect is the basis of gene suicide therapy success, where dying cells share toxic substrates via GJCs to neighbor cells, promoting massive cell death (Nardin et al, 2019).…”
Section: Role Of Cx43 In Melanomamentioning
confidence: 64%
“…It is suppressed in the tumor microenvironment. EPA improves chemosensitivity in murine melanoma by inducing connexin 43 expression, which is regulated by MAPK pathways [47]. In addition, DHA enhances the sensitivity of various tumor cells to ROS-inducing anti-cancer agents [48].…”
Section: Malignant Melanomamentioning
confidence: 99%
“…In addition, omega-3 PUFAs suppress tumor growth in melanoma [32,37,41,42,44,45] and squamous cell carcinoma [77], inhibiting migration and invasion in melanoma [33,34,37] and squamous cell carcinoma [81]. Omega-3 PUFAs also enhance the sensitivity to chemotherapy in melanoma [28][29][30][31][46][47][48] and radiosensitivity in squamous cell carcinoma [78]. Omega-3 PUFAs metabolites RvD1, RvD2, and RvE1 suppress debris-stimulated cancer progression in melanoma [50], and RvD2 reduces tumor size and cancer-derived cytokines/chemokines [76].…”
Section: Summary Of the Effect Of Omega-3 Fatty Acids Against Each Skin Cancermentioning
confidence: 99%